2010
DOI: 10.1159/000273066
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Adult Disease

Abstract: Variation in the quality or quantity of nutrients consumed during pregnancy can exert permanent and powerful effects upon the developing fetus. This programming of fetal development is emerging as a new risk factor for non-communicable diseases of adulthood, including coronary heart disease and the metabolic syndrome. Epidemiological studies show that indicators of nutritional deficit in pregnancy are associated with greater risk of diabetes and cardiovascular mortality. The study of programming in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(165 citation statements)
references
References 219 publications
2
150
0
13
Order By: Relevance
“…12 Although the underlying mechanism remains unknown, it is suggested to be because of programming changes in neurotransmitters and hormones secreted from the hypothalamus. 13 Furthermore, abnormalities in the lipid profile and insulin tolerance have been found in adolescents and adults born with low birth weights, possibly making them susceptible to metabolic syndrome. 14 Although glucose tolerance was not evaluated in the present study, LDL-C levels were significantly higher in children whose mothers smoked until the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although the underlying mechanism remains unknown, it is suggested to be because of programming changes in neurotransmitters and hormones secreted from the hypothalamus. 13 Furthermore, abnormalities in the lipid profile and insulin tolerance have been found in adolescents and adults born with low birth weights, possibly making them susceptible to metabolic syndrome. 14 Although glucose tolerance was not evaluated in the present study, LDL-C levels were significantly higher in children whose mothers smoked until the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…123 Low birth weight also may be related to the development of adult illness through epigenetic adaptation to intrauterine nutritional deficiencies (Barker hypothesis). 124 …”
Section: Effects Of Poverty Infant Mortality Adolescent Pregnancy Amentioning
confidence: 99%
“…Extensive epidemiologic studies have suggested that adult disease risk is associated with adverse environmental conditions early in development (Heijmans et al, 2008;Nijland et al, 2008;Swanson et al, 2009;Langley-Evans and McMullen, 2010;Warner and Ozanne, 2010). David Barker's group proposed the 'fetal origins' hypothesis that malnutrition at a very early age (in utero and in infancy) resulted in earlier and more severe adult chronic diseases (Barker, 2004(Barker, , 2007Barker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%